Risk factors for mortality in elderly and very elderly critically ill patients with sepsis: a prospective, observational, multicenter cohort study - Ignacio Martin-Loeches (Annals of Intensive Care, 2019)
Abstract Background Age has been traditionally considered a risk factor for mortality in elderly patients admitted to intensive care units. The aim of this prospective, observational, multicenter cohort study is to determine the risk factors for mortality in elderly and very elderly critically ill patients with sepsis. Results A total of 1490 patients with ≥ 65 years of age were included in the study; most of them 1231 (82.6%) had a cardiovascular failure. The mean age (± SD) was 74.5 (± 5.6) years, and 876 (58.8%) were male. The patients were divided into two cohorts: (1) elderly: 65–79 years and (2) very elderly: ≥ 80 years. The overall hospital mortality was 48.8% (n = 727) and was significantly higher in very elderly compared to elderly patients (54.2% vs. 47.4%; p = 0.02). Factors independently associated with mortality were APACHE II score of the disease, patient location at sepsis diagnosis, development of acute kidney injury, and thrombocytopenia in the group of elderly patients. On the other hand, in the group of very elderly patients, predictors of hospital mortality were age, APACHE II score, and prompt adherence of the resuscitation bundle. Conclusion This prospective multicenter study found that patients aged 80 or over had higher hospital mortality compared to patients between 65 and 79 years. Age was found to be an independent risk factor only in the very elderly group, and prompt therapy provided within the first 6 h of resuscitation was associated with a reduction in hospital mortality in the very elderly patients.